Upaya Meningkatkan Kemampuan Guru Sma Negeri 1 Tapung Hilir, Kabupaten Kampar Provinsi Riau Dalam Memanfaatkan Akun Belajar.Id Yang Terintegrasi Dengan Google Workspace For Education Melalui Workshop Penggunaan Teknologi Informasi Pada Kegiatan Pembelajar - sarpiati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Teachers at SMA Negeri 1 Tapung Hilir rarely know how to use a learning.id account with Google Workspace for Education. Researchers often find teachers struggling to use this information technology devices and asking for support from other teachers. Thus, a teacher's inability to use technology negatively impacts the learning process. To improve teachers' ability to use a learning.id account that is integrated with Google workspace for education, a workshop on the use of information technology in activities and learning will be held in 2020/2021. After the action research, data revealed an increase in teachers' ability to use their learning.id accounts. In cycle 1, instructors' capacity to use the learning.id account, which was connected with Google Workspace for Education, increased significantly. The findings of teacher-led exams on the usage of information technology show this trend. In the test, 26 (86.67%) got the predicate "Completed." The average teacher score was 81.15, with the lowest being 67. The top score was 89. Cycle II results indicated the greatest growth in instructors' capacity to use the learning.id account with the Google workspace for education. The findings of teacher-led exams on the usage of information technology show this trend. On the test, 100% of teachers got the predicate “Completed”. The average teacher score was 88.48, with the lowest being 78. While 9 was the highest